تفكيك الإلحاد في ضوء القرآن الكريم وما يترتَّب عليه من أحكام (Journal of the College of Basic Education, 2026)
This research aims to analyze atheism from a Quranic perspective. It begins by defining atheism and its causes, examining how the Quran addresses it, presenting means of prevention and treatment, and explaining the legal rulings that result from it. The research consists of an introduction, a preface, and three chapters, using an inductive and analytical approach.The preface addresses the technical definition of atheism, sheds light on its history and development in modern times, and explains the characteristics of contemporary atheism. The first chapter reviews the most prominent reasons behind the spread of atheism, such as psychological, social, and intellectual factors, while discussing the role of the media and digital openness in spreading these ideas.The second chapter deconstructs atheism in light of the Holy Quran, focusing on Quranic evidence for the existence of God Almighty. The research discusses the doubts promoted by atheists and how to respond to them using logical and rational Quranic methods. The study also addressed the effects of atheism on the individual and society according to the Quranic perspective.The third study was devoted to presenting means of preventing and treating atheism in light of the Holy Quran, including strategies for establishing correct belief, activating rational dialogue, and reviving human nature. It then outlined the legal rulings related to atheism.The study concluded that the Holy Quran provided comprehensive responses and precise treatment of atheism, using rational and transmitted methods. It emphasized the importance of religious and scientific education in preventing this phenomenon. The study also presented scientific recommendations and proposals to confront atheism, such as strengthening religious education and organizing scientific workshops and intellectual dialogues between religions and philosophies.